Analisis Postur Kerja Operator Sewing dengan Metode RULA untuk Mencegah Musculoskeletal Disorders dan Meningkatkan Kinerja - Mustaqim Mustaqim; Mohammad Riza Radyanto (Fakultas Teknik Universitas Tulang Bawang, 2026)
PT Fukuryo Indonesia is a garment manufacturing company. The garment industry is one of the labor-intensive manufacturing sectors and is highly dependent on human performance, especially sewing operators. The purpose of this study is to determine the level of risk of injury to sewing operators and can provide countermeasure ideas to improve performance quality. For this reason, it is necessary to analyze the work process with the aim of knowing the work posture of sewing operators with the Rapid Upper LimbAssessment (RULA) method and the Nordic Body Map (NBM) questionnaire. Based on the data processing that has been done from the calculation of the Nordic Body Map (NBM) questionnaire, there are sewing operators in the large merging section who have the highest score of 52. And the average score of the Rapid Upper LimbAssessment (RULA) method score is 4. Although a low score is obtained, changes are still needed for work postures. Changes must be made immediately to prevent posture fatigue when working for a long time, for this reason it is necessary to propose improvements to ergonomic seating chairs to minimize and prevent injuries. Keywords: Nordic Body Map, RULA, Sewing Operator, Work Posture